2011
DOI: 10.1152/ajplung.00214.2010
|View full text |Cite
|
Sign up to set email alerts
|

Increased deposition of chondroitin/dermatan sulfate glycosaminoglycan and upregulation of β1,3-glucuronosyltransferase I in pulmonary fibrosis

Abstract: Pulmonary fibrosis (PF) is characterized by increased deposition of proteoglycans (PGs), in particular core proteins. Glycosaminoglycans (GAGs) are key players in tissue repair and fibrosis, and we investigated whether PF is associated with changes in the expression and structure of GAGs as well as in the expression of β1,3-glucuronosyltransferase I (GlcAT-I), a rate-limiting enzyme in GAG synthesis. Lung biopsies from idiopathic pulmonary fibrosis (IPF) patients and lung tissue from a rat model of bleomycin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Although the primary cause of TGF-b hyperactivity in the cardiovascular lesions in a patient with MPS-I is unclear, increased TGF-b activity is known to up-regulate beta1,3-glucuronosyltransferase-I in fibroblasts, a rate-limiting enzyme in glycosaminoglycan synthesis, which leads to increase synthesis of glycosaminoglycans including dermatan sulfate, hyaluronic acid, and chondroitin sulfate A and C (Venkatesan et al 2011;Matalon and Dorfman 1968). It is also known that accumulated dermatan sulfate can activate STAT proteins which increase productions of elastindegrading proteins, i.e., matrix metalloproteinase-12 (MMP-12) and cathepsin S. (Ma et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary cause of TGF-b hyperactivity in the cardiovascular lesions in a patient with MPS-I is unclear, increased TGF-b activity is known to up-regulate beta1,3-glucuronosyltransferase-I in fibroblasts, a rate-limiting enzyme in glycosaminoglycan synthesis, which leads to increase synthesis of glycosaminoglycans including dermatan sulfate, hyaluronic acid, and chondroitin sulfate A and C (Venkatesan et al 2011;Matalon and Dorfman 1968). It is also known that accumulated dermatan sulfate can activate STAT proteins which increase productions of elastindegrading proteins, i.e., matrix metalloproteinase-12 (MMP-12) and cathepsin S. (Ma et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both animal and human cell culture models has demonstrated that modulation of hyaluronan occurs in the setting of infection and/or viral mimetics [84, 179]. Hyaluronan levels in lung tissue and bronchoalveolar lavage fluid (BALF) are elevated and correlate with the degree of inflammation in animal models of lung injury [139, 180, 181]. Furthermore, concentration of airway hyaluronan is higher in asthmatics and correlates with asthma severity [105, 134, 135, 138].…”
Section: Chronic Changes To Airway Ecm In Asthmamentioning
confidence: 99%
“…The PGs normally contribute to the mechanical stability of the collagen-elastin network and prevent collapse of alveolar structures caused by electrostatic interactions from the negatively charged GAGs (81). Structural remodeling of the lung resulting from abnormal expression of PG-GAG complexes and structural changes to the GAG side chains can contribute to the development of pulmonary diseases (45,(83)(84)(85)(86)(87)(88).…”
Section: Proteoglycansmentioning
confidence: 99%